1953
DOI: 10.1038/bjc.1953.32
|View full text |Cite
|
Sign up to set email alerts
|

The Life and Progression of Induced Skin Tumors in Mice

Abstract: BY studying the life of various kinds of spontaneous and induced tumors in animals, it has been found that they sometimes undergo irreversible changes in character. For example, a papilloma induced in mouse skin by applications of carcinogen, may become a carcinoma, so changing its character; or a spontaneous tumor of the mouse breast responding to pregnancy by an increase in growth rate may change its character and no longer respond to this stimulus. Foulds (1949stimulus. Foulds ( , 1950stimulus. Foulds ( … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0
1

Year Published

1956
1956
2007
2007

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(11 citation statements)
references
References 3 publications
2
8
0
1
Order By: Relevance
“…The results are reminiscent of those obtained by Shubik and Ritchie (1953) following one, two, or three applications of DMBA to the skin, followed by croton oil applications. They failed to obtain a progressive increase in tumour yield, in contrast to the earlier results of Berenblum and Shubik (1949) that increases in the concentration of the initiating agent did yield corresponding increases in the number of tumours produced.…”
Section: Discussionsupporting
confidence: 61%
“…The results are reminiscent of those obtained by Shubik and Ritchie (1953) following one, two, or three applications of DMBA to the skin, followed by croton oil applications. They failed to obtain a progressive increase in tumour yield, in contrast to the earlier results of Berenblum and Shubik (1949) that increases in the concentration of the initiating agent did yield corresponding increases in the number of tumours produced.…”
Section: Discussionsupporting
confidence: 61%
“…These lesions were very likely naturally occurring; however, the development of hyperplasia in response to continued shaving merits consideration. In this paper we provide evidence for the development of neoplasms from hyperplastic lesions, a progression that has been previously documented in mouse skin carcinogenesis studies (18)(19)(20). Since we have diagnosed squamous cell papillomas in nontreated mice, it is assumed that at least some ofthe hyperplastic lesions also occurred spontaneously in the SENCAR mouse.…”
Section: Histopathologysupporting
confidence: 54%
“…In these cases, the type of tumor and its malignant properties were generally easily recognizable. In one Matrix study, 18 of the 19 skin lesions diagnosed grossly as squamous cell carcinomas were microscopically confirmed as malignant neoplasms. Hennings (36) recently reported that more than 90% of the tumors diagnosed clinically as carcinomas were microscopically confirmed as squamous cell carcinomas.…”
Section: Correlation Of Gross and Microscopic Findingsmentioning
confidence: 99%
“…Detailed study of the present lesions seems to show a succession of stages leading up to true malignancy but failing to reach it during the lifetime of the mouse. This idea of progression has been developed by Foulds (1949,1950,1951) and by Shubik, Baserga and Ritchie (1953). The successful induction of true gastric carcinoma (Stewart and Lorenz, 1941, 1942 Howes and Oliviera, 1948; Stewart, Hare, Lorenz and Bennett, 1949;Stewart, Hare and Bennett, 1953) and of intestinal carcinoma (Lorenz and Stewart, 1940;Cox, Wilson and DeEds, 1947; Sandin, Miller and Rusch, 1955) shows that the progression can be speeded up by direct injection or by feeding of a carcinogen.…”
Section: Discussionmentioning
confidence: 99%